(untitled) (Iranian Journal of Kidney Diseases, 2020)
in the reports presented about COVID-19, patients receiving kidney transplantation have not been specifically studied and based on national flowchart, this population is classified as highrisk group, thus it is necessary to be aware of the step-by-step treatment approach of these patients. Suspicious cases included patients with a history of dry cough, chills or sore throat accompanying by shortness of breath with or without fever, patients with upper/lower respiratory symptoms with radiological manifestations as single or double-sided multilobular infiltrations on CT scan or plain chest radiography, any one that has a history of close contact with a definite COVID-19 case within the last 14 days, any one with a history of presence in COVID-19 epidemic regions within the last 14 days and patient with pneumonia that despite of proper treatment has an inappropriate clinical response and clinical condition becomes more severe in an unusual way or unexpectedly.